Menanamkan Nilai-Nilai Akhlak Mulia Pada Anak Usia Dini di Rumah Quran Alfatihah Kota Jambi - Nur Anisyah; Ria Maharani; Dini Kausari; Siti Marwah (Motekar: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
Qualitative research involving one of the teachers was conducted at Rumah Quran Alfatihah in Jambi City with the aim of shaping the noble moral values of early childhood through habituation. Documents, observations and interviews were used to collect data. The data was examined qualitatively by collecting information and making judgments. Based on the research findings, the Alfatihah Quran House prioritizes the virtues of morals through habituation, namely before and after activities, children should pray, be polite to parents and teachers by greeting and kissing hands, and studying and memorizing hadiths about the goodness values of noble morals. The research findings show the importance of educating early childhood in Alfatihah Quran House to uphold noble morals, namely instilling morals to Allah SWT and other humans. This moral cultivation has been going well and is carried out through exemplary, teaching, habituation, and providing motivation. Instilling noble morals through habituation in children is not only influenced by their cognitive, but also by their moral development. Good habits are important in the process of moral development, if good habits have been instilled since childhood then in his life will be reflected forms of good behavior. And of course the task of educators in this case parents or teachers must be able to introduce the concept of right or wrong, good or bad so that later children will understand and better understand the concept of good and bad.